Comparative Assessment of X-ray and CT Scan Effectiveness in Diagnosing Complex Pelvic Fractures Among Urban Road Traffic Accident Victims in Pakistan - Hasnain Ali, Muhammad Moueen, Madiha Naseer, Bushra Ujala, Sibtain Raza, Sajjad Rasool Chaudhary (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Complex pelvic fractures are life-threatening injuries frequently seen in road traffic accident (RTA) victims, especially in high-density urban regions. Early and accurate diagnosis is critical for reducing morbidity and mortality. Although X-ray remains the initial imaging modality due to accessibility and cost, its limitations in detecting complex fracture patterns raise concern. Computed tomography (CT) offers superior anatomical detail but is less widely available. This study aimed to compare the diagnostic performance of X-ray and CT in identifying complex pelvic fractures among RTA victims in urban Pakistan. Objective: To conduct a comparative analysis of X-ray and CT scan in detecting complex pelvic fractures in patients presenting after road traffic accidents in tertiary care hospitals of Islamabad and Lahore. Methods: A prospective comparative study was conducted from June 2022 to June 2023 at Shifa International Hospital, Islamabad, and Ittefaq Hospital, Lahore. Ninety adult patients with suspected pelvic trauma underwent both pelvic X-ray and CT scan. Fractures were classified using the Tile classification system. Radiological findings were assessed by independent radiologists, and diagnostic accuracy, sensitivity, specificity, and interobserver agreement were analyzed using CT as the reference standard. Results: CT scan detected complex pelvic fractures in 69 patients (76.7%) compared to 49 cases (54.4%) identified by X-ray. X-ray demonstrated 71.0% sensitivity, 95.0% specificity, and a positive predictive value of 97.9%. CT scan had 100% sensitivity and specificity. CT was significantly superior in identifying posterior ring, sacral, and acetabular fractures. Radiologists showed higher diagnostic confidence with CT (mean score 4.9 vs. 3.2) and greater interobserver agreement (κ = 0.93 for CT vs. κ = 0.68 for X-ray). Conclusion: CT scan outperforms X-ray in the accurate detection and classification of complex pelvic fractures in urban trauma settings. Its routine use should be integrated into emergency care protocols for RTA victims to ensure timely and accurate diagnosis, particularly in high-risk urban centers of Pakistan. Keywords: pelvic fractures, CT scan, X-ray, trauma imaging, road traffic accidents, Pakistan, Tile classification, emergency radiology